Professional Zakat in Contemporary Fiqh Discourse: An Epistemological Analysis and the Perspective of Maqāṣid al Sharī'ah - Muhammad Yusuf Siddik; Abdul Ghoni; Muhammad Sofwan Jauhari; Ahmad Muti (Yayasan Darussalam Bengkulu, 2026)
Background: This article aims to analyze the epistemological construction of professional zakat in contemporary fiqh discourse, examine the argumentative basis of its arguments, and evaluate its relevance in the perspective of maqāṣid al-sharī'ah and modern economics as a response to global economic structural transformation dominated by the service and professional sectors. Method: The research uses a qualitative approach with a descriptive-comparative analysis method of contemporary scholars' views on professional zakat. The analysis was conducted through a study of naqlī arguments (the Qur'an and hadith), 'aqlī arguments (qiyas and istinbat), and the maqāṣidī approach. Primary data sources included classical and contemporary fiqh literature, fatwas from scholars, and empirical research on the implementation of professional zakat in various Muslim countries. Results: The study identified three epistemological groups of scholars: mūjibūn (obligatory), mujīzūn ghayr mūjibīn (permissible without being obligatory), and māni'ūn (prohibited). The mūjibūn group, represented by Qaradawi and Az-Zuhaili, builds its argument based on the generality of the text (QS. Al-Baqarah: 267, QS. At-Taubah: 103), qiyas (analogy) to agricultural zakat, and the principle of distributive justice. The potential for professional zakat reaches 51.2% of the total national zakat potential, but the realization is only 8.3%, indicating a significant gap. From the maqāṣid perspective, professional zakat has ḍarūriyyah urgency to realize wealth redistribution and socio-economic justice. Conclusion: The implementation of professional zakat requires a comprehensive framework that integrates sharia principles with modern economic realities, strengthens the governance of zakat institutions, standardizes calculation mechanisms, and harmonizes with the taxation system to optimize the potential of zakat as a sharia-based fiscal instrument in poverty alleviation and inclusive economic development